2008
DOI: 10.1111/j.1526-4637.2007.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effects of a Combination of Static and Dynamic Magnetic Fields on Carpal Tunnel Syndrome

Abstract: PEMF exposure in refractory CTS provides statistically significant short- and longterm pain reduction and mild improvement in objective neuronal functions. Neuromodulation appears to influence nociceptive-C and large A-fiber functions, probably through ion/ligand binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 64 publications
0
31
0
1
Order By: Relevance
“…Another research trial applied combined static and dynamic magnetic fields for 4 h per day over two months. There was significant pain reduction, but only mild improvement in objective neuronal functions in the magnetic treatment group versus placebo [37]. This mode of treatment was not appropriate in the current study because of the need to avoid long-term exposure of the newborn to PEMF at home.…”
Section: Discussionmentioning
confidence: 80%
“…Another research trial applied combined static and dynamic magnetic fields for 4 h per day over two months. There was significant pain reduction, but only mild improvement in objective neuronal functions in the magnetic treatment group versus placebo [37]. This mode of treatment was not appropriate in the current study because of the need to avoid long-term exposure of the newborn to PEMF at home.…”
Section: Discussionmentioning
confidence: 80%
“…PEMF with magnetic field at the intensity of 200μT could increase the latency to thermal stimulation in land snails [22] and mice [23]. Magnetic field has been applied to improve neuronal recovery after injury, to lessen neuropathic pain [24], due to the stimulation of the central and peripheral neural systems. Pulsed magnetic field (PMF) has been used to treat the peripheral nerve injury for years, for it can accelerate the functional recovery of injured peripheral nerve [25].…”
Section: Discussionmentioning
confidence: 99%
“…PMF can ameliorate the hyperpolarization of after potentials and delayed depolarization of nerves [26]. PMF can also promote peripheral nerve regeneration in different experimental animal models [27; 28], because axons of neuron are sensitive to electrical and magnetic stimulation [24]. However, PEMF had no effect on the change of expression of HCN1 and HCN2 mRNA after CCI.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Several small studies have shown improvements in electrodiagnostic testing and pain scales with the use of magnetized wristbands. 4143 However, the research is preliminary, has methodological concerns, and only provides limited clinical information for treatment recommendations. Although magnet therapy cannot be recommended as treatment at this time for CTS, further research is important to better understand efficacy, dose, and duration.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%